Private Wealth in Renaissance Florence - Goldthwaite, Richard A. (Book collections on Project MUSE., 1968)
The histories of six generations of the Strozzi, Gondi, Guicciardini, and Capponi families are traced from the fifteenth to the mid-sixteenth centuries by focusing on the family household as defined by the economic bonds reflected in account books. These four families were among the best known of the city's patriciate and were influential in affairs of the city. Their histories serve as case studies in seeking to determine the nature of the patrician family as a specific kind of social institution and to assess its importance in Florentine history. A concluding chapter attempts to relate the changing composition of the family to the general development of Renaissance civilization. Originally published in 1968. The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.